2015
DOI: 10.1001/jama.2015.1108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sedative Premedication on Patient Experience After General Anesthesia

Abstract: clinicaltrials.gov Identifier: NCT01901003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 35 publications
0
114
1
7
Order By: Relevance
“…Moreover, after appropriate investigations, AA might be used to treat pre-operative anxiety in surgical patients, constituting serious alternative for benzodiazepines, commonly used for this purpose in clinical practice [9,10,23]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, after appropriate investigations, AA might be used to treat pre-operative anxiety in surgical patients, constituting serious alternative for benzodiazepines, commonly used for this purpose in clinical practice [9,10,23]. …”
Section: Resultsmentioning
confidence: 99%
“…Research among patients who received general anesthesia and were given lorazepam, placebo or no premedication, showed that premedication with lorazepam did not improve the experience of patients, but was associated with a longer time for extubation and a lower rate of early cognitive recovery. This research casts doubt on the routine use of lorazepam for premedication in patients undergoing general anesthesia 16. However, Scavée et al17 investigated the impact of fear and anxiety on the outcome of vascular surgery and suggested that fear and anxiety increase the incidence of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing anxiety is a serious concern for the improvement of patient experience during the perioperative period. A previous study about anxiolytic premedication failed to demonstrate any improvement in patient experience,2 suggesting that treating surgery-induced anxiety as an illness may not be the answer. Besides anxiety, a patients’ need for information is an important aspect that should be addressed because of its weight in the patient global experience of the perioperative period.…”
Section: Contextmentioning
confidence: 97%